2003
DOI: 10.1046/j.1523-1747.2003.12013.x
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Pulse Imaging of ex vivo Basal Cell Carcinoma

Abstract: Terahertz pulse imaging has been used for the first time to study basal cell carcinoma ex vivo, the most common form of skin cancer. This noninvasive technique uses part of the electromagnetic spectrum in the frequency range 0.1-2.7 THz. A total of 21 samples were imaged; the study was performed blind and results were compared to histology. Each image consisted of possible diseased tissue and normal tissue from the same patient. The diseased tissue showed an increase in absorption compared to normal tissue, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
203
0
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 404 publications
(211 citation statements)
references
References 35 publications
(38 reference statements)
0
203
0
8
Order By: Relevance
“…These results indicate that histopathological diagnosis using optical microscopy may be replaced by THz images in the future. Previous reports indicate that, especially in basal cell carcinoma, different kinds of tissues are clearly distinguishable in THz images due to THz transmittance variation (Knobloch et al 2002;Woodward et al 2002aWoodward et al , 2002bWoodward et al , 2003Wallace et al 2004a). Recently, Fitzgerald et al (2006) reported the possibility of breast cancer diagnosis using THz images with a fresh, nonfixed tissue specimen as well as a paraffin specimen.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results indicate that histopathological diagnosis using optical microscopy may be replaced by THz images in the future. Previous reports indicate that, especially in basal cell carcinoma, different kinds of tissues are clearly distinguishable in THz images due to THz transmittance variation (Knobloch et al 2002;Woodward et al 2002aWoodward et al , 2002bWoodward et al , 2003Wallace et al 2004a). Recently, Fitzgerald et al (2006) reported the possibility of breast cancer diagnosis using THz images with a fresh, nonfixed tissue specimen as well as a paraffin specimen.…”
Section: Discussionmentioning
confidence: 99%
“…These tendencies are also applicable to normal myocardial tissue, necrotic or degenerated lesions, and scar lesions in which collagen fibers are dominant. There have been several reports of a clear contrast in THz images between cancer and normal tissues (Knobloch et al 2002;Woodward et al 2002aWoodward et al , 2002bWoodward et al , 2003. As important factors that influence the absorbance of THz waves in basal cell carcinoma (BCC), Woodward et al described the roles of water contained in tissues and the difference of cell density between the tumor and normal regions in the skin (Woodward et al 2002a(Woodward et al , 2002b(Woodward et al , 2003.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations